Prevalence of smoking and its associated factors among university staff - Fasoro, Ayo Akin; Gyanchand Rampal, Lekhraj Rampal; Mohd Sidik, Sherina; Md Said, Salmiah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2013)
Globally, one person dies every six seconds as a result of tobacco use. This makes tobacco use the cause of every one out of 10 deaths in adults and the single largest and leading cause of preventable death in the world. The objective of this study was to determine the prevalence of smoking among staff of Universiti Putra Malaysia. For the purpose of this study an analytical cross sectional study design was used and a standardized, pre-tested, while a validated well-structured questionnaire was used for data collection. The prevalence of smoking was found to be 10.0% (26.5% among males and 0.5% among females). In addition, significant associations were found between smoking and gender, religion, marital status, highest educational level, occupation, and family income (p < 0.05). In particular, gender and educational level were significant predictors of smoking. In conclusion, the prevalence of smoking among university staff was shown to be considerably lower than that stated for the national level. However, the University could aim at achieving zero prevalence in the years to come.